Mental effort and recovery from task-induced fatigue in people with traumatic brain injury. Issue 2 (16th January 2023) - Bruijel, Jessica; Vermeeren, Annemiek; Stapert, Sven Z.; van Heugten, Caroline M.
Abstract: Purpose: This exploratory case-controlled study examined whether the same amount of effort leads to similar feelings of fatigue and whether feelings of fatigue decline at the same rate in people with traumatic brain injury (pwTBI) compared to controls. Methods: Twenty pwTBI and 20 healthy controls (HC) completed an adaptive n -back task to induce fatigue and reported mental effort upon task completion and state-fatigue pre-task and several times during 30-minutes rest-period post-task. Task difficulty adapted to performance allowing both groups to invest substantial amounts of mental effort. Results: Fatigue and effort levels were higher in pwTBI compared to controls. Multiple linear regression analyses showed that effort was positively related to post-task fatigue and this relationship did not differ between groups. Pre-task fatigue was the only predictor of post-task fatigue. Multilevel models showed no significant difference in decline of fatigue over the rest-period between groups. Conclusions: Excessive feelings of fatigue following TBI could not be explained by a higher vulnerability to the fatigue-inducing effects of mental effort needed to perform a specific task. In pwTBI pre-task fatigue levels might be more related to the complex demands of everyday life. Future studies should investigate recovery of fatigue and applications of this knowledge to rehabilitation interventions. Implications for rehabilitation: People with TBI experience long-term fatigue as one of the most frequent and disabling symptoms and this long-term fatigue is a risk factor for development of secondary psychiatric symptoms such as depression or anxiety. Since people with TBI did not show a higher vulnerability to the fatigue-inducing effects of mental effort, fatigue following TBI might be better explained by the complex demands of everyday life such as external (environment) and internal (emotions) factors. Rehabilitation programs should be directed to this complex and highly individual interplay of fatigue in relation to other factors.